Kualitas Produk, Citra Merek dan Electronic Word of Mouth terhadap Keputuusan Pembelian Produk EigerKualitas Produk, Citra Merek dan Electronic Word of Mouth terhadap Keputuusan Pembelian Produk Eiger - Agil Riroj Abdul Rohman; Agus Budi Santosa (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the influence of Product Quality (Variable X1), Brand Image (Variable X2) and Electronic Word of Mouth (Variable X3) on purchasing decisions for Eiger products. The method used in this research is quantitative methods. The data collection technique used by researchers in this research is using primary data obtained through distributing questionnaires and literature study. Data analysis techniques start from data preparation, data tabulation to the testing stage. Based on the results of research calculations, multiple linear regression analysis. The coefficient of determination (R2) value can be obtained from the variables product quality (X1), brand image (X2) and electronic word of mouth (X3) which influence 77.2% (0.772) of the product decision (Y), the remaining 22.8 % influenced by other factors outside this research. In conclusion, product quality and brand image have a positive and significant effect on purchasing decisions, while electronic word of mouth has no effect on purchasing decisions Keywords: Brand Image, Electronic Word Of Mouth, Product Quality